'Art is different': Material practice, learning and co-making at The Social Studio. (1st March 2020) - McQuilten, Grace; Spiers, Amy
This article examines the relationship between traditional and creative research methods through the case study of The Social Studio (TSS), an art-based social enterprise in Melbourne, Australia. TSS aims to address systemic barriers to employment and education for people from refugee and migrant backgrounds through training and work experience in fashion and textiles. Specifically, the article reflects on the embodied, co-making learning space and model of TSS which addresses some of the barriers faced by migrant and refugee students in accessing formal education. Our research brings together traditional research methods, such as interviews and observation, as well as a creative workshop where both research subjects and researchers were taught a weaving activity. The article reflects critically on the limitations of traditional research methods, the challenges of researching in creative community contexts and also the need to document and analyse how material and embodied experiences impact on social and community development.